2018
DOI: 10.1111/add.14280
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parental drinking on alcohol use in young adults: the mediating role of parental monitoring and peer deviance

Abstract: Background/Aims Evidence demonstrating an association between parental alcohol use and offspring alcohol use from robust prospective studies is lacking. We tested the direct and indirect associations between parental and young adult alcohol use via early alcohol initiation, parental monitoring and associating with deviant peers. Design Prospective birth cohort study. Path analysis was used to assess the possible association between parental alcohol use (assessed at 12 years) and alcohol use in young adults (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 39 publications
2
47
0
2
Order By: Relevance
“…Parental smoking, alcohol use, and marijuana use are associated with increased use of the same drugs by offspring. [1][2][3][4][5][6][7] The intergenerational transmission of nonmedical prescription opioid (NMPO) use from parent to child has not previously been examined. The role of the family in adolescent NMPO use has been inferred from the finding that onethird of youth report that a family member was the source of their prescription opioids.…”
mentioning
confidence: 99%
“…Parental smoking, alcohol use, and marijuana use are associated with increased use of the same drugs by offspring. [1][2][3][4][5][6][7] The intergenerational transmission of nonmedical prescription opioid (NMPO) use from parent to child has not previously been examined. The role of the family in adolescent NMPO use has been inferred from the finding that onethird of youth report that a family member was the source of their prescription opioids.…”
mentioning
confidence: 99%
“…Peer pressure is certainly one of the most striking in uences, especially when it appears predominantly in the social repertoire of the individual. Its magnitude gains de nitive contours from late adolescence (15 years), weakening after adulthood 14,35,40 . In the present study, the predominance of alcohol and drunkenness, marijuana and crack use among the participants' friends was related to the early onset of crack use.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies with psychoactive substances have shown that the earlier the age of onset of consumption -beginning with alcohol and tobacco -the greater the likelihood to develop addiction to this substance, more serious consumption patterns and more problematic deviant behaviors 12,13 . Detaching the risk factors related to the age of onset of consumption allows not only environmental assessment for prevention strategies as well as speci c control strategies, both of them based on scienti cally based information 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations